ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI - Ali Syarifudin, Retno Susanti & Sutarno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this research is to analyze the significance of the influence ofservice quality, price, consumer satisfaction to the customer loyalty as well as theinfluence of service quality to the purchase customer loyalty with satisfaction as aintervening variable. The population is all consumers who visit and buy at WarungMakan Bu Yati Solo. 100 respondents are selected as sample, using purposive sampling.This research uses survey method, the type data collection with interview, questionnaireand observation. Data analysis used test instruments, classic assumption test, pathanalysis, t test, F test, the coefficient of determination. The result is there servive qualityhave signifcants effect to the cunsumers satisfaction, service quality have significantseffect to the customer loyalty, consumers satisfaction have significance to the customerloyalty, consumers satisfaction mediates the relationship of service quality to thecustomers loyalty. Adjusted R2 on multiple linear regression analysis is 33,4% and theresult of path analysis with sobel test is 0,036 with the value of t 1,98.Keywords: service quality, consumer satisfaction, customer loyalty